THE USE OF LITERACY-INSTRUCTIONAL CATEGORY TO IMPROVE STUDENTS’ READING COMPREHENSION - Setiarini Setiarini (Universitas Islam Negeri Walisongo Semarang, 2016)
This investigation examined the use of Literacy-Instructional Category on students’ reading comprehension. Particularly, there are two objectives of the study. The first is to explore the students’ writing improvement when they engaged in the first cycle of reading activities by employing literacy instructional categories. The second is to explore the students’ reading comprehension by using instructional categories. Thirty students from English Department of IAIN Salatiga participated in the study and they were in the third semester. A classroom action research was employed to answer the research problems. Three cycles were done to complete this action research. Based on the score result gathered from the cycles, the students’ reading comprehension improved. The student’s scores were not more than sixty because they did not understand intensively rereading activities in cycle one. But students’ score increased in cy- cle two and cycle three. In cycle three, rereading activities followed transformed practice (critical framing) lead the better improvement in their reading comprehension.